The Level of Psychological Adjustment Among a Sample of Female Breast Cancer Patients in Riyadh Province and Its Relationship to Self-Esteem - Al-Otibi, Eman Mohammad Sharee (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identify the level of psychological adjustment and the level of self-esteem and the relationship between them among women with breast cancer in Riyadh Province, and it also aimed to identify the differences in each of these psychological adjustment and self-esteem levels according to the variables “period of injury, age, and educational level.” The study used the descriptive-correlational method. The study included 44 female breast cancer patients from Riyadh Province. To collect data, the Psychological Adaptation Scale, prepared by Al-Shakir (2003), and the Self-Esteem Scale, prepared by Coopersmith, were used. To answer the questions of the study, a number of statistical methods were used: arithmetic means, standard deviations, weight percentiles, Pearson’s Correlation Coefficient, Kruskal-Wallis, and Mann-Whitney. The study found that the dimensions of psychological adjustment (personal combability, family combability, and social combability) and the total score of the scale came at a high level, whereas, the health adjustment dimension was at an average level for women with breast cancer, and there were statistically significant differences in the work dimension of the self-esteem scale according to the age variable in favor of the older age group (50 years and over) versus the younger age group (40 years and less).The study recommended paying attention to psychological support programs for breast cancer patients, and involving them in recreational and sports activities and events to enhance their psychological compatibility and self-esteem.
Keywords: psychological adjustment; self-esteem; breast cancer